2017
DOI: 10.1186/s12877-017-0584-3
|View full text |Cite
|
Sign up to set email alerts
|

Regular group exercise contributes to balanced health in older adults in Japan: a qualitative study

Abstract: BackgroundWhile community-wide interventions to promote physical activity have been encouraged in older adults, evidence of their effectiveness remains limited. We conducted a qualitative study among older adults participating in regular group exercise to understand their perceptions of the physical, mental, and social changes they underwent as a result of the physical activity.MethodsWe conducted a qualitative study with purposeful sampling to explore the experiences of older adults who participated in regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 27 publications
(26 reference statements)
5
35
0
2
Order By: Relevance
“…Support and feedback provided by the instructor may have helped participants to gauge further progress, serving as an enhanced motivator [46,47]. Furthermore, participation in group-based programs has been reported to increase adherence, improve psychological status (e.g., self-esteem), and enhance socializing [40,47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Support and feedback provided by the instructor may have helped participants to gauge further progress, serving as an enhanced motivator [46,47]. Furthermore, participation in group-based programs has been reported to increase adherence, improve psychological status (e.g., self-esteem), and enhance socializing [40,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Physical performance is suggested to improve in a group setting, probably because within group ‘comparative’ feedback improves motor learning skills [63]. In terms of the psychosocial aspect, group exercise enhances motivation, improves self-esteem and enjoyment as well as enhances socializing factors, which are all crucial for exercise adherence [48,49,65,66,67,68,69]. All these attributes are involved in the motor learning process, which forms the essence of physical performance [65].…”
Section: Discussionmentioning
confidence: 99%
“…Regular exercise can also increase confidence, self-esteem and reinforce positive behaviours if the physical changes that occur create a sense of achievement. In older adults, regular group exercise has been shown to increase feelings of social connection within a community and the mutual social support can contribute to sustaining physical activity in the long term [43,44]. As such, exercise-based interventions may be beneficial for reducing both social and psychological frailty.…”
Section: Exercise and Cognitive Functionmentioning
confidence: 99%
“…Meanwhile, other research has emphasized that older people can maintain health by achieving social capital through social engagement via activities such as group exercise [14]. Furthermore, our previous work have already found that older adults can achieve balanced health in the physical, mental, and social domains through regular group exercises as part of a community-wide PA intervention, which also contributed to community expansion through social connectedness and mutual support [15]. Leaders within the senior-citizen community thus play essential roles in generating social capital.…”
mentioning
confidence: 96%